A Clinical Case Report-Lekhana Basti and Kati Basti in Gridhrasi w.s.r Sciatica - Gurav, Narendra M; Bagade, Subhas V (International Research Journal of Ayurveda & Yoga, 2022)
Background: Gridhrasi is one of the most common disorders of Vata, which closely resembles with sciatica, which is characterized by pain or discomfort associated with sciatic nerve. The prevalence of sciatica varies considerably ranging from 3.8% in the working population to 7.9% in the nonworking population. Contemporary medicine has limitations giving short-term relief in pain or surgical intervention with side effect. Aim and Objectives: The aim of this study was to access the efficacy of Ayurvedic management including Shodhana and Shamana Chikitsa in Gridhrasi. Materials & methods: A male patient aged 43years who was already diagnosed with intervertebral disc prolapsed in L4-L5, correlated with Gridhrasi 3years approached to our hospital and was treated with Panchakarma treatment including Lekhana basti, Kati vasti, and virechana along with Shamana Chikitsa. The treatment was continued for consecutive one month. Results: Symptomatic assessment of patient was carried out after one month and satisfactory outcome was there and overall quality of life of patient was significantly improved. Conclusion: The aforementioned therapy gives symptomatic relief for the management of Gridhrasi.